2015
DOI: 10.5379/urbani-izziv-en-2015-26-supplement-010
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactorial GIS-Based Analytical Method to Determine the Quality of Urban Green Space and Water Bodies

Abstract: The type, size, and spatial distribution of public green spaces and water bodies are key factors for the microclimatic quality of urban areas, particularly within densely built-up districts, where they influence the quality of life. The analytical method presented in this paper looks at entire cities in a GIS-based approach that identifies potential critical areas of the city (with regard to heat stress or the accessability of green spaces) and quantifies their size and location in relation to green space and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The benefits of public spaces for cities and its users are listed by much research and many case studies from all around the world, demonstrated by quantitative and qualitative measurements by researchers such as Armour et al (2014); Deilmann et al (2015); Högyeová et al (2019) or Kuttler et al (2012). The following paragraphs will now synthesise the information about the benefits of public spaces from the most relevant theoretical literature research papers and studies.…”
Section: The Value Of Public Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of public spaces for cities and its users are listed by much research and many case studies from all around the world, demonstrated by quantitative and qualitative measurements by researchers such as Armour et al (2014); Deilmann et al (2015); Högyeová et al (2019) or Kuttler et al (2012). The following paragraphs will now synthesise the information about the benefits of public spaces from the most relevant theoretical literature research papers and studies.…”
Section: The Value Of Public Spacesmentioning
confidence: 99%
“…Vegetation helps to reduce this imbalance and brings many important benefits for urban areas. In London, Deilmann and colleagues measured a 4-11 °C temperature decrease in the buildings with green walls (Deilmann et al, 2015). Natural and artificial water element also reduce the temperature in inhabited areas, as the water surface is generally cooler than ambient air.…”
Section: The Value Of Public Spacesmentioning
confidence: 99%
See 1 more Smart Citation